STUDY ON TICKS AND HAEMOPARASITIC DISEASES OF LOCAL CATTLE IN MALAKAND AGENCY - N. Ahmad; H. A. Hashmi; S. A. Khan (Journal of Animal and Plant Sciences, 2006)
Ticks infestation and piroplasmosis are serious problems of domestic cattle. The present study was conducted to find out the prevalent species of’ ticks and the piroplasms transmitted by these ticks in Malakand Agency (NWFP) Pakistan. The effect of ticks and blood parasites on various blood parameters was also studied. The parameters included: RBC count, WBC count, Haemoglobin (Hb) estimation, erythrocytic sedimentation rate (ESR) and differential leukocytic count (DLC). A total of 80 cattle were selected. Each type was divided into four groups i.e. A. B, C and D. The cattle of group-A were free from any infestation/infection. The animals of group- B were only ticks infested. Animals of group-C were only piroplasm infected and the animals of group-D were infested with ticks and the piroplasms. Each group consisted of 20 animals. Haemotological examination revealed a significant decrease (P<0.05) in TEC, Hb and TLC in group-B, C and D as compared to group-A. The lymphocytes were decreased from normal in all test groups, significantly. However, neutrophils and eosinophils were increased significantly in test groups as compared to control group (A). The values of erythrocytic sedimentation rate (ESR) showed a significant increase in groups B.C and D as compared to the control group (A). The overall results showed that the effect of mixed infection on haematology was greater than the single infection of ticks or piroplasm.
Keywords: Haemoparasitic diseases; pisoplasmosis; Haemoglobin; Erythrocytic sedimentation ratio (ESR); differential lenkocytic count